A continuum mechanical, bi‐phasic, two‐scale model for thermal driven phase transition during solidification. Issue 1 (21st October 2015) - Moj, Lukas; Ricken, Tim; Steinbach, Ingo
Abstract: This articel focuses on a bi‐scale numerical description for solidification process simulation. The macro‐scale implies two phases which are the solid and liquid metallic alloy physical states described using the theory of porous media (TPM) enhanced by strong thermal coupling and finite elastic‐plastic‐creep temperature dependent material behaviour. Furthermore, a linear viscous melt as well as a laminar melt flow are adopted. The thermal driven physics of solidification is covered by a microscopic phase‐field model. Therefore, a Ginzburg‐Landau type free energy function is employed. After discussing the main model details, a real Bridgman oven numerical pre‐model will demonstrate the principal performance. (© 2015 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)